BUDAYA PERILAKU BERSIH DI DESA PENGLIPURAN BALI - Fathorrahman Fathorrahman (Jurnal Sosiologi Reflektif, 2020)
This paper outlines a role model for cleanliness preservation in community life in the Penglipuran village of Bali. Using a cultural approach, the Penglipuran village can raise the awareness of its citizens to participate in creating clean behavior. Along with the emergence of awareness of citizen participation, in the village of Penglipuran there are also local traditions that help guard the creation of clean behavior among its citizens. The existence of Penglipuran village which in 2018 has been named the third cleanest village in the world by bombastic magazine, is certainly interesting to study. To explore further roles of the Penglipuran village in preserving clean behavior, this research focuses on several questions: What is the cultural portrait of the Penglipuran community so that it is conducive to civilizing clean behavior? How do people participate in preserving cleanliness in the Penglipuran environment? What is the role of local actors in instilling a culture of clean behavior for their citizens? These three questions are analyzed with a sociological approach. As for the technique to obtain the data, this study uses empirical studies by observing and meeting several key informants and important informants to be interviewed. Tulisan ini menguraikan sebuah role model pelestarian kebersihan dalam kehidupan masyarakat yang ada di desa Penglipuran Bali. Dengan menggunakan pendekatan budaya, desa Penglipuran bisa membangkitkan kesadaran warganya untuk berpartisipasi dalam menciptakan perilaku bersih. Beririsan dengan munculnya kesadaran partisipasi warga, di desa Penglipuran juga terdapat tradisi lokal yang turut mengawal terciptanya perilaku bersih di kalangan warganya. Keberadaan desa Penglipuran yang pada tahun 2018 dinobatkan sebagai desa paling bersih ketiga di dunia oleh Bombastic Magazine, tentu menarik untuk diteliti. Untuk menelusuri lebih jauh bagaimana peran desa Penglipuran dalam melestarikan perilaku bersih, penelitian ini fokus pada beberapa pertanyaan: apa potret kultural masyarakat Penglipuran sehingga kondusif dalam membudayakan perilaku bersih? Bagaimana partisipasi warga dalam melestarikan kebersihan di lingkungan Penglipuran? Bagaimana peran aktor lokal dalam menanamkan budaya perilaku bersih bagi warganya? Ketiga pertanyaan ini dianalisis dengan pendekatan sosiologis. Adapun teknik untuk memperoleh datanya, penelitian ini menggunakan studi empiris dengan cara mengobservasi dan menemui beberapa informan kunci dan informan penting untuk diwawancarai.